2021
DOI: 10.1017/s0950268821002247
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of COVID-19 vaccine in preventing infection and disease severity: a case-control study from an Eastern State of India

Abstract: Effectiveness of corona virus disease-19 (COVID-19) vaccines used in India is unexplored and need to be substantiated. The present case-control study was planned to elicit the effectiveness of COVID-19 vaccines in preventing infection and disease severity in the general population of Bihar, India. This case-control study was conducted among people aged ≥45 years during April to June 2021. The cases were the COVID-19 patients admitted or visited All India Institute of Medical Sciences (AIIMS), Patna, Bihar, Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…Our results are in line with the findings reported by Singh et al where individuals with FV had a lower likelihood of having severe disease on initial presentation to the hospital (18.2%) compared to PV (31.8%) and unvaccinated (42.6%) cases (P 0.022). 23 Overall, FV patients were found to have a lower likelihood of experiencing severe disease (30.3%) during their illness compared to PV (51.3%) and unvaccinated (54.1%) cases in the same study (P 0.035). 23 Similarly, Mhawish et al reported more patients from the non-immunized group to have higher severity categories while fewer non-immunized individuals were in the lower severity categories compared to immunized people.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our results are in line with the findings reported by Singh et al where individuals with FV had a lower likelihood of having severe disease on initial presentation to the hospital (18.2%) compared to PV (31.8%) and unvaccinated (42.6%) cases (P 0.022). 23 Overall, FV patients were found to have a lower likelihood of experiencing severe disease (30.3%) during their illness compared to PV (51.3%) and unvaccinated (54.1%) cases in the same study (P 0.035). 23 Similarly, Mhawish et al reported more patients from the non-immunized group to have higher severity categories while fewer non-immunized individuals were in the lower severity categories compared to immunized people.…”
Section: Discussionmentioning
confidence: 66%
“… 23 Overall, FV patients were found to have a lower likelihood of experiencing severe disease (30.3%) during their illness compared to PV (51.3%) and unvaccinated (54.1%) cases in the same study (P 0.035). 23 Similarly, Mhawish et al reported more patients from the non-immunized group to have higher severity categories while fewer non-immunized individuals were in the lower severity categories compared to immunized people. 24 In addition, the same study found that at least one dose of immunization was related to a diminished odds of higher severity scale (OR 0.2; P < 0.001).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As infections increased, it became clear that the Delta strain dominated the vaccine breakthrough cases (1,2). While the overall efficacy of the approved Indian vaccines was low for Delta infections, their effectiveness in preventing severe infections ranged from 70% ->90% depending on the population (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…As no vaccine is 100% effective, some vaccinated individuals get infected [ 3 ]. However, it is expected that these individuals will have a less severe form of infection, less frequent hospitalization, and intensive care unit (ICU) admission.…”
Section: Introductionmentioning
confidence: 99%